2020
DOI: 10.3389/feduc.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

Constructions of Leadership Identities via Narratives of African Women School Leaders

Abstract: The paper explores African women school leaders' constructions of their leadership identity. Using self-perception theory which sees changes in self-perceived leadership skills and dispositions as being related to changes in perceived leader identity, constructions of African women's leadership identity are mapped over a lifelong career. Leader identity is, in this sense, inextricably linked to gender and an attempt is therefore made to understand these leader identities as gendered. The paper presents an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Values are a central explanation for women's desire to advance in their careers (Jenni, 2017). According to Moorosi (2020), the values and characteristics shaped their approach to leadership amongst African female school principals.…”
Section: Corporate Culture and Dynamicsmentioning
confidence: 99%
“…Values are a central explanation for women's desire to advance in their careers (Jenni, 2017). According to Moorosi (2020), the values and characteristics shaped their approach to leadership amongst African female school principals.…”
Section: Corporate Culture and Dynamicsmentioning
confidence: 99%
“…Imm and Wahid (2020) observed that enduring hardships led to their participants becoming "resilient, persevering, courageous, and resourceful" (p. 211). Moorosi (2020) claimed the hardships one woman went through early in life "shape [d] her resilience and strength as a leader [. .…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…The leader's identity with the gender lens has been analyzed in many dimensions. The research was done based on particular nationalities, e.g., China (Chen, 2018), France (Saint-Michel, 2018), India (Datta & Agarwal, 2017;Reutzel et al, 2018), Indonesia (Hudson et al, 2020), sub-Saharan Africa (Moorosi, 2020), South Africa (Bornman, 2019;Herbst, 2020), the U.S. (Ko et al, 2015;Peachey & Burton, 2011;Yun et al, 2020) or in the intra-national perspective. Researchers used the following approaches in area of leader's identity: gender and leader's effectiveness (Collica-Cox & Schulz, 2020; Ko et al, 2015;Rhee & Sigler, 2015), gender and the pursuit of innovation opportunities (Reutzel et al, 2018), gender and leadership style (Bornman, 2019;Brands et al, 2015;Rhee & Sigler, 2015), gender and communication style (Violanti & Jurczak, 2011), gender and errors/mistakes (Thoroughgood et al, 2013), gender and external audience response to organizational failures (Montgomery & Cowen, 2020), gender and stereotypes and prejudices (Parker et al, 2020;Rhee & Sigler, 2015;Saint-Michel, 2018), gender and looking for help (Rosette et al, 2015), gender and narcissism (Chen, 2018), gender and leader's behavior and emotions (Schreiner et al, 2018;Yun et al, 2020), gender and behavioural integrity (Gatling et al, 2020), gender and personal and professional identity transitions (Meister et al, 2017), gender and conflict (Veldman et al, 2017).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%